2014
DOI: 10.1177/1060028014560012
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis

Abstract: A review of the current evidence reveals a need for prospective, randomized controlled studies to provide more definitive conclusions on steroid use in patients with SJS, TEN, and/or overlap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
1
30
0
3
Order By: Relevance
“…Systemic corticosteroids, however, have shown variable success in reducing both ocular sequelae and patient mortality. 52 In comparative studies, the impact of high-dose pulsed systemic corticosteroids on ocular outcomes ranges from no benefit to possible benefit. 37,38,53 The systemic impact of corticosteroids is even more variable, with no benefit, increased complications including sepsis, and a mortality benefit all being reported.…”
Section: Othersmentioning
confidence: 99%
“…Systemic corticosteroids, however, have shown variable success in reducing both ocular sequelae and patient mortality. 52 In comparative studies, the impact of high-dose pulsed systemic corticosteroids on ocular outcomes ranges from no benefit to possible benefit. 37,38,53 The systemic impact of corticosteroids is even more variable, with no benefit, increased complications including sepsis, and a mortality benefit all being reported.…”
Section: Othersmentioning
confidence: 99%
“…Systemic corticosteroids (22), intravenous immunoglobulin (IVIG) (23), and cyclosporine (24) are often used to treat CTL-mediated SCARs; however, the clinical outcomes of these therapies remain controversial (25,26). Recently, several studies revealed that treatment with anti-TNF-α biologic agents appeared beneficial in patients with TEN and TEN-like acute cutaneous lupus erythematosus (17,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Preclinical Testing Of Etanercept: Ex Vivo Testing For Potenmentioning
confidence: 99%
“…For SJS/TEN, corticosteroids are the cornerstone of treatment albeit efficacy remains unclear. Despite improved knowledge of the immunopathogenesis of these conditions, immune-modulatory therapies currently used have not been definitively proved to be efficacious [49, 107], and new strategies are urgently needed.
Fig. 3Management of patients with a suspected drug induced exfoliative dermatitis
…”
Section: Discussionmentioning
confidence: 99%
“…In SJS, SJS/TEN and TEN the efficacy of corticosteroids is far from being demonstrated. Recently, a meta-analysis based on 6 retrospective studies evaluating the role of corticosteroids alone or together with IVIG has been published [107]. In this study, 965 patients were reviewed.…”
Section: Management and Therapymentioning
confidence: 99%